2004
DOI: 10.1007/s00540-004-0240-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic ATP infusion improves spontaneous pain and tactile allodynia, but not tactile hypesthesia, in patients with postherpetic neuralgia

Abstract: This study demonstrated that repetitive intravenous ATP infusion could improve spontaneous continuous pain and paroxysmal pain, as well as improving tactile allodynia, but did not influence tactile hypesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…The analgesic property of intravenous ATP demonstrated in the present and previous clinical studies [3][4][5][6] appearred to be in contrast to the algogenic or pronociceptive property of peripherally or spinally administered ATP, shown in experimental studies [10]. It is quite conceivable that the analgesic effects of intravenous ATP observed in the present study are those of adenosine via A1 receptor activation, because ATP is extremely rapidly converted to adenosine by ectoenzymes when given intravenously [2,11,12].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The analgesic property of intravenous ATP demonstrated in the present and previous clinical studies [3][4][5][6] appearred to be in contrast to the algogenic or pronociceptive property of peripherally or spinally administered ATP, shown in experimental studies [10]. It is quite conceivable that the analgesic effects of intravenous ATP observed in the present study are those of adenosine via A1 receptor activation, because ATP is extremely rapidly converted to adenosine by ectoenzymes when given intravenously [2,11,12].…”
Section: Discussioncontrasting
confidence: 79%
“…Actually, in our recent double-blind study with ATP, complete abolition of spontaneous pain and/or allodynia lasting for more than 15 months was achieved with a single session of ATP therapy in 2 out of 12 patients with NP post-PE,TE [34]. In addition, patients experiencing pain relief with adenosine or ATP lasting for days (>48 h) are not rare [4,[13][14][15]17,18], and such patients are considered to be good candidates for repetitive treatment with adenosine or ATP infusion [15], which may provide progressively improving pain relief [5,18]. Further, one study has revealed that a significant reduction in the mean pain scale persisted for at least 2 weeks after a single session of adenosine infusion in 23 patients with adenosine-responsive neuropathic pain [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the response to adenosine and ATP may vary among patients because of differences in pathophysiological mechanisms underlying the PHN pain. In recent report of eight PHN patients, spontaneous pain and tactile allodynia were significantly reduced by intravenous ATP infusion at a much lower dose (16.7 mg·kg -1 ·min -1 over 60 min) [73] than the dose we used (100 mg·kg -1 ·min -1 or less over 120-180 min) [21,66,67]. Therefore, dose-response studies may be required to determine an optimal ATP infusion dose for each of the various pain conditions.…”
Section: Atp For Chronic Pain Patientsmentioning
confidence: 87%
“…Therefore, sufficiently high doses of ATP infusion over a long period of time (e.g., 2-3 h) may provide better pain relief than shorter infusions (e.g., 1 h or less). It is noteworthy that in a limited number of cases, permanent abolition of spontaneous pain and allodynia can be achieved with a single adenosine or ATP infusion [10,21,50,52,53,67], and that repeated adenosine or ATP infusions provide progressively improved pain relief in some responders [51,73]. K, ketamine; L, lidocaine; ATP, adenosine triphosphate Positive response to a drug was defined as more than 50% reduction in the Visual Analogue Scale for spontaneous pain a V, C, T, L, and S indicate trigeminal, cervical, thoracic, lumbar, and sacral regions, respectively b The response to ATP was correlated with the response to ketamine but not with the response to lidocaine Modified from [66], with permission, by adding data from three cases including one in [21] Positive drug response Fig.…”
Section: Atp For Chronic Pain Patientsmentioning
confidence: 99%